Optimalisasi Tele-Supervisi dalam Pendokumentasian Asuhan Keperawatan di Ruang Rawat Inap Rumah Sakit: Suatu Program Inovasi - Fitri Alfisah; Rr. Tutik Sri Hariyati; Laurentia Dewi (Journal of Telenursing (JOTING), 2022)
This study aims to encourage and improve the quality of nursing care through an innovation program in optimizing supervision in the documentation of nursing care. The method used is an innovation program with a pilot study through a problem solving approach. The innovation program was carried out on the head of the room and team leader who were recruited through purposive sampling using questionnaires, observation sheets and interviews. The results showed that: 1) the problem identification stage, need improvement in the quality of nursing care documentation; 2) the implementation stage, it is necessary to develop a nursing care guide, a checklist form for the quality of documentation, socialization, mentoring and testing of Tele-Supervision; 3) the evaluation stage, the results of the supervision of the documentation of nursing care have been carried out perfectly and completely by the implementing nurse through a trial of the Tele-Supervision form. In conclusion, improving the quality of nursing care documentation needs to be controlled with the implementation of scheduled supervision by the head of the room. Keywords: Nursing Care, Nursing Documentation, Innovation, Tele-Supervision